Pembelajaran Terintegrasi di SMP: Menghubungkan Disiplin Ilmu Dan Membentuk Pemahaman Holistik - Fatia Aziza; Lisa; Rachel Fauzal Karima; Salmah Hayaty (Interdisciplinary Explorations in Research Journal, 2024)
Integrated learning helps students understand disciplines holistically, such as integrating history into mathematics education, combining physics concepts and information and communication technology (ICT), integrating religious knowledge with social subjects, and applying sports knowledge in learning. The journal also highlights the important role of foreign languages in the understanding of science and the relationship between art and natural science. The integration of science not only enhances students' understanding of mathematical principles and ICT skills, but also shapes their character, develops an understanding of social and spiritual values, and increases awareness of cultural diversity. Through the integration of knowledge, students can be ready to face future challenges with a broader perspective. The method of data collection in this journal is carried out through an approach that utilizes relevant sources, ensuring the accuracy and linkage of data with the research subject..